2011
DOI: 10.1590/s0100-29452011000500060
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do padrão de visitação de Apis mellifera em três cultivares de meloeiro, em Petrolina-PE, Brasil

Abstract: RESUMO -Para o cultivo do meloeiro, a presença de abelhas no período de florescimento é fundamental para garantir a polinização e incrementar a produção de frutos. Nesse sentido, o presente trabalho teve por finalidade verificar se há diferenças no comportamento de visitas e no recurso floral forrageado por Apis mellifera, em três cultivares de meloeiro. O trabalho foi desenvolvido no Campo Experimental da Embrapa Semiárido, em Petrolina-PE, com as cultivares do tipo amarelo (BRS Araguaia), pele-de-sapo (P-33)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 2 publications
3
11
0
Order By: Relevance
“…Analyzing the mean values of the times observed, for most hybrids, anthesis was registered after 6:00 a.m., in both floral types, with no difference for anthesis times between male and hermaphrodite flowers, agreeing with the literature (ABREU et al, 2008;KIILL et al, 2011). The opening of the flowers early in the morning is indicative of flowers pollinated by bees; this is regarded as a leading characteristic of the melittophily syndrome (RECH et al, 2014).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Analyzing the mean values of the times observed, for most hybrids, anthesis was registered after 6:00 a.m., in both floral types, with no difference for anthesis times between male and hermaphrodite flowers, agreeing with the literature (ABREU et al, 2008;KIILL et al, 2011). The opening of the flowers early in the morning is indicative of flowers pollinated by bees; this is regarded as a leading characteristic of the melittophily syndrome (RECH et al, 2014).…”
Section: Resultssupporting
confidence: 90%
“…In a comparative analysis on melon hybrids in the region of Juazeiro (BA), Kiill et al (2011Kiill et al ( , 2012 claimed that the highest visitation observed to hermaphrodite flowers may be related to the attractiveness of the pollinator. also, the authors commented that the floral morphology may have influenced the visitation pattern of A. mellifera in studies conducted in intercropped crops.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing melon hybrids, it was found that flowers of Sancho were more attractive to A. mellifera, indicating that simultaneous cultivation of both hybrids could result in competition for pollinator attraction. However, with regard to the behavior of A. mellifera throughout the day, it was that for both hybrids, a lower number of visits occurred during the early morning, which was also observed by Kiill et al (2011Kiill et al ( , 2012, in the municipality of Petrolina, state of Pernambuco, Brazil in different cultivars of melon. However, the opposite was observed by Sousa (2008) and Sousa et al (2012) in studies with this cucurbit in the region of Acaraú, state of Ceará, Brazil.…”
supporting
confidence: 75%
“…(P-33) and Cantaloupe (Can-4) cultivars, Kiill et al (2011) found differences in relation to visitation peak of A. mellifera and the floral type visited, yet no differences were observed in relation to foraged resource by the bees. The present study was, therefore, carried out to verify if there are differences in the frequency and foraging behavior of the floral visitors in the melon hybrids (10:00 -'Yellow-melon' and Sancho 'Piel de Sapo') of a commercial area in the municipality of Juazeiro, state of Bahia, Brazil.…”
mentioning
confidence: 79%
“…Concerning the period of time of resources collection, the pattern showed in Figure 1 was similar to that found by Kiill et al (2011), in the same region, with different types of melon. Sousa et al (2012) studied honeybee activities on yellow melon flowers in the state of Ceará and found similar results as well, that is, initial collection of P and then N, although with greater differences and at other times (from 11 a.m.).…”
Section: Discussionsupporting
confidence: 74%